Molecular dynamics simulations of ligand-induced backbone conformational changes in the binding site of the periplasmic lysine-, arginine-, ornithine-binding protein - Yang, A.; Mancera, Ricardo (Kluwer Academic Publishers, 2008)
The periplasmic lysine-, arginine-, ornithine-binding protein (LAOBP) traps its ligands by a large hinge bending movement between two globular domains. The overall geometry of the binding site remains largely unchanged between the open (unliganded) and closed (liganded) forms, with only a small number of residues exhibiting limited movement of their side chains. However, in the case of the ornithine-bound structure, the backbone peptide bond between Asp11 and Thr12 undergoes a large rotation. Molecular dynamics simulations have been used to investigate the origin and mechanism of this backbone movement. Simulations allowing flexibility of a limited region and of the whole binding site, with and without bound ligands, suggest that this conformational change is induced by the binding of ornithine, leading to the stabilisation of an energetically favourable alternative conformation.